THERMODYNAMIC EFFICIENCY CLOSED AND BACK (IDEAL) CYCLES OF INTERNAL COMBUSTION ENGINES USING BIOFUELS - Бойко, Т.; Кондратюк, Г. (Science-based technologies, 2010)
Calculated ideal thermodynamic cycles of internal combustion engine when using different types of liquid biofuels. It is shown that a decrease in the heat of combustion of biofuels be proportionally reduced the specific work cycle and the average engine power and increases in proportion to the unit cost of fuel and mean effective pressure.